Life imprisonment in Singapore: legal and sociological perspectives - Tan, Benny (Life Imprisonment in Asia, 2023)
This chapter focuses first on describing the key crimes in Singapore for which life imprisonment is a sentencing option and the jurisprudence of the Singapore courts on when life imprisonment will be imposed where it is an option. Special attention is paid to cases involving: (a) the choice between imposing the death penalty and life imprisonment; (b) imposing life imprisonment and a shorter term of imprisonment; and (c) life imprisonment for young offenders. In the latter portion of the chapter, some brief sociological perspectives on life imprisonment in Singapore are also offered. Specifically, the life of a person sentenced to life imprisonment in Singapore and the relevant post-release regime are described.